Circulating Neutrophil-to-Lymphocyte Ratio Predicts Stroke-Associated Infection and Poststroke Fatigue Affecting Long-Term Neurological Outcomes in Stroke Patients - Lei Zuo; Leiyu Geng; Yujia Cao; Xin-yu Zhou; Wu Di; Yun Liu; Zhe Zhong; Dandan Liu; Zhengsheng Zhang; Fuling Yan (Mediators of Inflammation)
Conclusions: Higher NLR levels in the acute phase of stroke might indicate a higher incidence of SAI and PSF. Therefore, higher NLR is associated with a poor stroke prognosis.